Pengaruh Pendekatan Open-Ended Problem terhadap Berpikir Kritis Matematis Siswa - Kharisma Br Brahmana (Sepren, 2020)
This study aims to determine the effect of the Open-ended problem learning approach on students' critical mathematical thinking on the matter of quadratic equations and functions in class IX SMP Santo Xaverius 2 Kabanjahe. This type of research is a quasi-experimental research with the research population that is all students of class IX SMP Santo Xaverius 2 Kabanjahe. With the purposive random sampling technique, the research sample for class IX-A consisted of 35 students, but due to the pandemic, only 10 students were included. The instrument used was a post-test question in the form of an essay question that had been tested for instrument validation and a student response questionnaire regarding the application of the Open-ended problem learning approach. After conducting the research, the post-test average was 74.86 with a standard deviation of 21 , 34 and the mean score of the student response questionnaire was 74.4 with a standard deviation of 5.14. The results of the normality test indicate that X and Y are normally distributed. Furthermore, the regression and correlation tests were carried out with α = 0.05. From this test, it was concluded that there was a significant effect of the Open-ended Problem learning approach on students' mathematical critical thinking on the material of equations and quadratic functions for class IX SMP Santo Xaverius 2 Kabanjahe. After learning in the classroom, a questionnaire was given to students' responses regarding the Open-end problem approach and the final score was obtained with a good assessment category.